Habitat and Spatio-Temporal Interaction Between Green Peafowl with Cattle and Megaherbivores in Baluran National Park - Satyawan Pudyatmoko (Jurnal Ilmu Kehutanan)
Green peafowl (Pavo muticus muticus) is an endangered species, whose population is continuously declining. It is protected animal in Indonesia that occurs in remnant, and sometime small habitat with high hunting pressure, that made the animal prone to extinction. This study was conducted to investigate the influence of habitat on the occupancy probability of green fowl as well as the interaction between green peafowl and free-range cattle and wild mammal in Baluran National Park. The presence of animals in the study was recorded by camera traps, and the habitat variables were measured in the locations, where the camera traps were installed. The research found that the occupancy of green peafowl best explained by the model that not include any habitat variables. The pattern of interaction between green peafowl and domesticated cattle was similar to those of between green peafowl and the majority of wild mammal. There was no evidence of negative impact of domesticated cattle on the spatial occurrence as well as temporal activity of green peafowl. Green peafowl is a bird species with high adaptability to various environmental conditions. The population decrease of this animal in Java might be mainly due to high hunting pressure than habitat change.